Synthesis of ballad and romantic and lyrical poems in V. Mykolaitis-Putinas’ poetic works - Balčius, Jonas (Literatūra, 1973)
The present paper deals with the problems of specification of poetry genres in Lithuanian literature. The introduction of it contains a short historical outline of their development. On the basis of the analysis of V. Mykolaitis-Putinas’ poetic works, an attempt is made to investigate the properties of each poetry genre and the essential factors determining the development of his ballads as synthesis of romantic and lyrical poems. The author of the present paper tries to prove that V. Mykolaitis-Putinas’ poetic works were created under the influence of the principles of romanticism and symbolism and the latter account for the further development of his ballads and the synthesis of romantic and lyrical poems.